Social Emotional Learning in Chemistry Learning : Group Investigation dan Contextual Learning Integration to Develop Student’s Social Emotional Competencies - Maulidya Virginanti; Yuli Rahmawati; Fera Kurniadewi (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
This article presents the results from integrating Social Emotional Learning (SEL) through cooperative learning and contextual approach in chemistry learning. This study was conducted on 10th-grade students in the academic year of 2016/2017. Collaborative learning, as well as the use of real-life scenario, are some of the teaching practices for facilitating Social Emotional Learning (SEL) and promotes students' social-emotional competenciesthat aligned with affective competencies in Indonesia’s 2013 curricula. The proposed teaching practices also answer the challenges faced by the implementation of the 2013 curricula, finding proper teaching practices to integrate to develop student’s character through learning activity. The empirical work of the study is based on a qualitative approach. Six Group Investigation’s stage integrated with the use of real-life scenario was analyzed through various method such as observations, interviews, reflective journals, and student’s worksheets answer. The results found that students showed positive attitudes and perspective’s change towards chemistry learning, establish positive relationship with peers, cooperative skill, tolerance, and responsible decision making by considered himself, others, and community within the learning process.